The Traffic Signal of Inland Waterways - Amine Monaf El-Khalfiy; Choirul Anam (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2020)
To control and regulate inland shipping traffic the use of inland waterways is needed. Signs inland voyages that are used are taken and determined based on UN ECE International provisions, which have been adapted for use in Indonesia based on a manual on inland waterway traffic signs in Indonesia in accordance with the RI Minister of Transportation Decree. NO. PM.3 / L / PHB - 77 DATE 18 MAY 1977.